Development of a Portable Solar Generator - Khairil Yusri Bin Mohd Yusoff; Syed Mohammed Uddin; Mohd Izhar A Bakar (Journal of Engineering Technology, 2022)
This study aims to develop a portable solar generator system. One of the considerable aspects is to design a suitable solar tracking system and create a suitable sizing for the system. In addition, the dissimilarity between the type of photovoltaic modules was studied to make sure the Solar Energy Generation Systems (SEGS) operates with the most effective type of photovoltaic (PV) module. The Battery Storage System is protected and controlled by a charge controller. The outcomes from the result obtained for power comparison between the single axis and dual axis clearly shows that the dual axis can improve the efficiency of the solar panel by moving and tracking the movement of the sun. Charging mobile phones and laptops show that the inverter was correctly chosen and it was able to support the power needed by the load. From the experiment conducted throughout the development of the work, the portable solar generator manages to charge mobile phones and laptops.